Thyroid dysfunction and pregnancy outcomes - Sima Nazarpour; Fahimeh Ramezani Tehrani; Masoumeh Simbar; Fereidoun Azizi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Pregnancy has a huge impact on the thyroid function in both healthy women and those that have thyroid dysfunction. The prevalence of thyroid dysfunction in pregnant women is relatively high. Objective: The objective of this review was to increase awareness and to provide a review on adverse effect of thyroid dysfunction including hyperthyroidism, hypothyroidism and thyroid autoimmune positivity on pregnancy outcomes. Materials and Methods: In this review, Medline, Embase and the Cochrane Library were searched with appropriate keywords for relevant English manuscript. We used a variety of studies, including randomized clinical trials, cohort (prospective and retrospective), case-control and case reports. Those studies on thyroid disorders among non-pregnant women and articles without adequate quality were excluded. Results: Overt hyperthyroidism and hypothyroidism has several adverse effects on pregnancy outcomes. Overt hyperthyroidism was associated with miscarriage, stillbirth, preterm delivery, intrauterine growth retardation, low birth weight, preeclampsia and fetal thyroid dysfunction. Overt hypothyroidism was associated with abortion, anemia, pregnancy-induced hypertension, preeclampsia, placental abruption, postpartum hemorrhage, premature birth, low birth weight, intrauterine fetal death, increased neonatal respiratory distress and infant neuro developmental dysfunction. However the adverse effect of subclinical hypothyroidism, and thyroid antibody positivity on pregnancy outcomes was not clear. While some studies demonstrated higher chance of placental abruption, preterm birth, miscarriage, gestational hypertension, fetal distress, severe preeclampsia and neonatal distress and diabetes in pregnant women with subclinical hypothyroidism or thyroid autoimmunity; the other ones have not reported these adverse effects. Conclusion: While the impacts of overt thyroid dysfunction on feto-maternal morbidities have been clearly identified and its long term impact on childhood development is well known, data on the early and late complications of subclinical thyroid dysfunction during pregnancy or thyroid autoimmunity are controversial. Further studies on maternal and neonatal outcomes of subclinical thyroid dysfunction maternal are needed.